산후우울증의 한의학적 치료에 대한 임상연구 동향 분석 - 국내 증례 보고를 중심으로 - 백준기; 안나겸; 박해모; Jun Gi Beak; Na Gyeoum Ahn; Haemo Park (대한예방한의학회지, 2025)
Objectives : This study was conducted to analyze the clinical research status of Korean medicine for postpartum depression, focusing on domestic case reports. Methods : The studies were searched from KISS, RISS, OASIS, SCIENCEON. The year of publication, type of study, demographic information of participants, intervention type and details, outcome measurements and treatment results of the finally selected studies were analyzed. Results : 7 studies have been collected. In herbal medicine 'Series of Ansin-tang', acupuncture at 'PC6', 'HT7', 'GV20' moxibustion at 'CV4', psychotherapy such as 'LiGyeungByunQi-therapy', and 'Giungoroen-therapy' were most frequently used in treatment on postpartum depression. 'Edinburgh Postnatal Depression Scale (EPDS)' was most frequently used in outcome measurements. In all studies, Korean medicine treatment improved postpartum depression symptoms. Conclusions : This study revealed that various Korean medicine treatments were effective for postpartum depression. Based on this, it can be used for the clinical setting of postpartum depression and the direction of future research. However, it is thought that it is necessary to secure a higher level of evidence for Korean medicine treatment of postpartum depression through a more systematic study that reinforces the limitations of this study.